Preference for injectable over oral HIV pre-exposure prophylaxis in public-sector primary-care clinics in Swaziland - Siedner, Mark J.; Hettema, Anita; Hughey, Allison; Oldenburg, Catherine E.; Kohler, Stefan; Bärnighausen, Kate; McMahon, Shannon; Jia, Chuan; Lejeune, Charlotte; Matse, Sindy; Bärnighausen, Till (AIDS <London>, 2018)
: Long-acting injectable (LAI) HIV pre-exposure prophylaxis (PrEP) may mitigate adherence challenges reported by young women in Southern Africa. We assessed preferences for PrEP in public-sector, primary care clinics in Swaziland. Among surveyed respondents, 75% (95% confidence interval=65-83%) stated preference for LAI over oral PrEP; with no differences by sex, age, or sexual behavior (all P>0.05). Notably, over 70% (95% confidence interval 58-82%) with current use of oral PrEP also stated preference for LAI PrEP.
Gesehen am 01.10.2019